(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the profile and work processes of professionals working in the Stroke Care Line. Methodology: this is an exploratory, qualitative-quantitative study which was developed from December 2021 to April 2022, in an administrative district of the city of Belém-PA. Twenty-seven college-educated professionals working in the line of stroke care participated in the research, a questionnaire with open and closed questions was applied. Results: 27 participants answered the survey questionnaire, 44.4% are nurses; 33.3% are physicians, 3.7% are Social Service professionals and 18.5% are Health Managers. 74.1% were female, with a predominance in the age group between 25 and 30 years, where professional nurses were also the ones with the highest number. Regarding the professional bond, it was found that physicians had a greater number of bonds as a civil servant (CLT) when compared to other professionals. Regarding the time of professional training, 37% reported having up to 4 years of training and 44.4% said they had been working for up to 4 years. 55.6% of the participants have specialization. 85.2% reported having experience in Assistance Management. 55.6% stated that they have knowledge about the technologies used in health. Regarding the protocol that is most used in the Cerebral Vascular Accident (CVA) Care Line. The Manchester Protocol was the most mentioned by health professionals. This protocol is widely used in the urgency of health services, but it is not specific for the stroke care line, but for the classification of disease risks. Regarding the existence of a sequential flow described in the health unit for stroke care, 75.0% of the participants reported that it does not exist and 8.3% are unaware of it. Conclusion: Health professionals, when providing patient care, in view of the complexity of stroke, have their knowledge and professional practice constantly challenged. Therefore, it is necessary to establish greater access to technological information in workplaces, with tools that can produce better results in the assistance provided.